When You Have to Retire at 55: Prospect and Learning Agenda - Mazanah Muhamad (Adult Education Research Conference, 2002)
Forty to fifty four years old Malaysian public employee view mandatory retirement at 55 as challenging. They expect to be financially and social psychologically affected. Pre-retirement learning program is wanting. Their learning interest reflects their biopsychosocial situation, value and needs. Learning for these middle age adults can be framed to life-stage issue and context.